Kratom-Associated Pulmonary Toxicity: A Systematic Review of Case Reports and Forensic Series with a Proposed Clinical Phenotype Classification - Venkatkiran Kanchustambham; Swetha Saladi (Journal of Medical Toxicology, 2026)
Abstract Introduction Kratom use has increased, including concentrated 7-hydroxymitragynine products, but pulmonary toxicity has not been systematically synthesized. Methods We systematically reviewed human case reports, conference abstracts, and forensic/autopsy series describing pulmonary outcomes after kratom, mitragynine, or 7-hydroxymitragynine exposure (PROSPERO CRD420261427143). Five databases were searched through 24 June 2026. Two reviewers independently screened, extracted, and appraised reports; causality was graded using Naranjo criteria for clinical reports and WHO-UMC criteria for forensic reports. Synthesis was narrative. Results Twenty-four reports were included: 14 clinical and 10 forensic. Five categories were identified in two tiers: primary pulmonary syndromes—diffuse alveolar hemorrhage ( n = 3), acute respiratory distress syndrome (ARDS)/diffuse acute lung injury ( n = 3), and eosinophilic/hypersensitivity pneumonitis ( n = 2)—and secondary consequences of systemic toxicity—central respiratory depression ( n = 6) and post-mortem pulmonary edema/congestion ( n = 10). All clinical patients survived; all forensic decedents died. Attribution was Probable in 9 reports, Possible in 13, and Unlikely in 2. Pulmonary edema/congestion was the most common forensic finding but was nonspecific; single-agent fatalities had high mitragynine concentrations (2,325–7,500 ng/mL). Conclusions Reported kratom-associated pulmonary presentations cluster into five provisional, hypothesis-generating categories spanning primary lung injury and secondary systemic effects. Clinicians should consider kratom and 7-hydroxymitragynine in unexplained acute lung injury, alveolar hemorrhage, eosinophilic pneumonitis, or opioid-type respiratory depression; targeted toxicology and standardized reporting are needed to refine this framework. Registration PROSPERO CRD420261427143.